Review: God in the Dock: Dialogic Tension in the Psalms of Lament - Eaton, J. H. (Journal of Semitic studies, 2005)
God in the Dock: Dialogic Tension in the Psalms of Lament Carleen Mandolfo , (Journal for the Study of the Old Testament Supplement Series 357). Continuum, London 2002. x + 222. Price: £50.00 . ISBN: 0-8264-6200-6